Differential expression of CD133 based on microsatellite instability status in human colorectal cancer. Issue 1 (12th October 2012) - Park, Jae Jun; Kwon, Ji‐hee; Oh, Sun‐Hee; Choi, Junjeong; Moon, Chang Mo; Ahn, Joong Bae; Hong, Sung Pil; Cheon, Jae Hee; Kim, Tae Il; Kim, Hoguen; Kim, Won Ho; DiGiovanni, John
Abstract The association between the types of genomic instability and cancer stem cell (CSC) has not been elucidated. We aimed to investigate the expressions of CSC markers with respect to microsatellite instability (MSI) status in human colorectal cancer (CRC). Immunostainings for CD133, CD44, and CD166, and K‐ras mutation analysis were performed on 50 MSI‐high (MSI‐H), and 50 microsatellite stable (MSS) CRC tissues. In 11 MSS and MSI‐H CRC cell lines, CD133 expression and DNA methylation statuses of the CD133 promoter were determined. The proportion of CD133 positive cells and the ability of colosphere formation were compared between HCT116 cells and HCT116 + Chr3 cells (hMLH1‐restored HCT116 cells). Immunohistochemistry for CSC markers revealed that high CD133 expression was more frequent in MSS cancers than in MSI‐H (P < 0.001, 74.0% vs. 28.0%, respectively), and related with short disease‐free survival. Neither CD44 nor CD166 expression differed significantly with respect to MSI status. K‐ras mutation showed no association with expressions of CD133, CD44, or CD166. CD133 expression was relatively high in the MSS cell lines compared to those in MSI‐H, and showed a reverse correlation with DNA methylation of the CD133 promoter. hMLH1‐restored HCT116 cells increased proportions of CD133 positive cells and colosphere forming ability, compared to those in HCT116 cells. In conclusion, high levels of CD133 expression were observed more frequently in MSS CRC than in MSI‐H, suggesting that differential expression of colon CSC markers may be linked to tumor characteristics dependent on MSI status. © 2012 Wiley Periodicals, Inc.